ASSESSMENT SUPERVISOR COURSES STUDENTS AGAINST MASTERY OF AUTOCAD SMKN 2 SOLOK CONDUCTING PRAKERIN IN ACADEMIC YEAR 2015/2016 - 1867-1882 , Anggi Yuda Saputra (Universitas Negeri Padang, 2016)
This research was motivated by the presence of students who did not master AutoCAD while executing Prakerin. As this study aims to reveal how the assessment supervisor to student mastery of AutoCAD SMKN 2 Solok implementing Prakerin in the academic year 2015/2016. Type of this research is quantitative descriptive study using total sampling technique, the sample population was replaced by the research subjects. The subjects were students do Prakerin supervisor amounting to 12 people in different places with the number of students as many as 38 people. The data collection technique using a questionnaire using Likert Scale. For data analysis using Microsoft Excel and descriptive analysis techniques with percentage and mean. The results of this study indicate that the ratings field supervisors on student mastery of AutoCAD SMKN 2 Solok implementing Prakerin in the academic year 2015/2016 in seven indicators: Drawing with Software with mean 3.60, Drawing Concrete Columns with mean 2.80, Drawing Concrete Beams with a mean of 2.79, Draw a floor plate with a mean of 2.61, with a mean of 2.80 Drawing construction Stairs, Drawing Construction Sky-langitdengan mean 2.88, Drawing retaining walls with mean 2.57. Based on the average overall assessment supervisor field against mastery AutoCAD SMKN 2 Solok 2,87categorized quite mastered. Keywords: Assessment, supervisor, mastery, AutoCAD, Prakerin.